Stability of adhesive interface different adhesives applied to dentin - Fabianni MagalhÃes Apolonio (2009)
There is a general consensus that resin-dentin bonds created by contemporary hydrophilic dentin adhesives deteriorate over time. One way to predict how resin-dentin interface would behave over time is aging the specimens in vitro by immersion in different solutions. The objective of this study was to evaluate the effect of immersion in NaOCl solution on the bond interface created by different adhesive systems. For this, it was used 28 human third molars that had superficial dentin exposed and composite build-ups were built on its surface using one of those adhesives, etch-and-rinse: Scothbond Multi-purpose and Single Bond, or self-etch: Clearfil SE and Adper SE. Specimens were cut into nontrimming dentin-composite beams to microtensile testing. After a period of 24 h in distilled water, sticks from each tooth were divided equally into two groups: control or aged in 10% NaOCl for 1 h. Beams were pulled until failure at crosshead speed of 1 mm/min and bond strength was calculated. Fractured sticks were analyzed and classified in: mixed fracture, cohesive in dentin and cohesive in composite; and expressed in percentage. Data from ÂTBS test were statistically analyzed using Kruskal-Wallis and Games-Howell tests. For comparison between control and aging groups was used the Mann-Whitney test (α=0.05). Two specimens from each adhesive were used to investigate the effect of NaOCl on the interfacial morphological characteristics. For that, specimens were cut in only one direction, dentin-resin discs were fixed in a glass-holder and ground with SiC papers under running water. Slices were treated by Massonâs trichrome acid staining technique to evidence collagen exposed zones and analyzed by optical microscopy. ÂTBS results showed that NaOCl solution significantly reduced bond strength comparing with the control groups for all adhesives tested. Scothbond MP (control: 39,95Â12,72; aged: 26,45Â9,90 MPa) showed the highest values and Adper SE (control: 13,21Â3,15; aged 4,95Â2,49) the lowest in both control and aging groups. Clearfil SE (control : 27,02Â6,84; aged: 16,17Â3,79) and Single Bond (control : 26,66Â8,35; aged: 11,77Â4,28) showed no difference in control groups, but after aging, Clearfil SE showed better results. Microscopic images analysis showed that NaOCl acts efficiently on degradation of collagen fibrils for all adhesive systems. Conclusion: Aging in 10% NaOCl solution reduces bond strength and modifies the interfacial morphological characteristics of the adhesive systems tested.